DEVELOPMENT OF COST INDEX FOR OFFSHORE PLATFORM DECOMMISSIONING FOR MALAYSIAN WATERS - AHMED, BABA ABDULLAHI (2015)
Offshore platforms decommissioning hasbecome a central issue in the oil andgas industry in recent times. The burden of decommissioning earlierplatforms which did not incorporate the costs of decommissioning in their concession agreements with operators falls squarely on national governments. However, in recent concession contracts, operators are nowmandated to set aside an annual amount into a special account created specifically to cater for decommissioning at the end of the concession or economic life of the platform. However, a common challenge facing the industry is determining accurate decommissioning costs for offshore platforms. Afurther challenge is thefact that no twoplatforms are the same, thereby introducing an element of uncertainty into current estimates. Hence taking this into cognizance, a model was designed to enumerate a range rather than an exact cost estimate.